The Zahrawain Method in Primary Education: A Systematic Review of Implementation Strategies - Muhammad Faruq Hanafi; Sarafuddin Sarafuddin; Rizqi Istiqomah (Journal of Educational Sciences, 2026)
This qualitative study investigates the implementation and effectiveness of the Zahrawain method for Quranic memorization (tahfidz) in three Islamic elementary schools in Central Java, involving teachers, students, and parents as participants. The study highlights the importance of innovative memorization techniques for young learners and aims to describe how the Zahrawain method is applied, identify its supporting and inhibiting factors, and evaluate its impact on students’ memorization ability. Data were collected through observations, interviews, and document analysis. The findings show that the Zahrawain method, which integrates audio-visual media and repetitive talqin, results in an average memorization rate of 5–7 verses per month, with 70% of students successfully meeting their targets. Supporting factors include teacher competence in tajwid, parental involvement, and adequate technological access, while challenges arise from students’ concentration difficulties and limited resources in certain areas. The study concludes that the Zahrawain method has strong potential to enhance tahfidz learning when accompanied by structured teacher training and equitable resource support. This research contributes empirical evidence for a multisensory memorization approach aligned with contemporary pedagogical practices.